2022
DOI: 10.1016/j.imu.2021.100825
|View full text |Cite
|
Sign up to set email alerts
|

A new COVID-19 intubation prediction strategy using an intelligent feature selection and K-NN method

Abstract: Background Predicting severe respiratory failure due to COVID-19 can help triage patients to higher levels of care, resource allocation and decrease morbidity and mortality. The need for this research derives from the increasing demand for innovative technologies to overcome complex data analysis and decision-making tasks in critical care units. Hence the aim of our paper is to present a new algorithm for selecting the best features from the dataset and developing Machine Learning(ML) based models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Similarly, ref. [15][16][17][18]23] found age as one of the key features for predicting intubation in COVID-19 patients. However, Bae et al [18] used radiomics features and two demographic features (age and gender) to predict mortality and ventilator support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, ref. [15][16][17][18]23] found age as one of the key features for predicting intubation in COVID-19 patients. However, Bae et al [18] used radiomics features and two demographic features (age and gender) to predict mortality and ventilator support.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the second study, CXR and radiomic data were used and found that the integration of radiomic data improved the early prediction of mortality. Aljouie et al [15] achieved an AUC of 0.83 and a balanced accuracy of 0.80 using RF. Meanwhile, in Bae et al's study [18], the DL model achieved an AUC of 0.83, sensitivity of 0.79, and specificity of 0.74.…”
Section: Ai-based Studies To Predict Early Mortality In Covid-19 Pati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Its accuracy mainly focuses on clinical blood samples applying a statistical t-test for filtering unique pandemic diagnosis tools for positive cases. [7] 3D representation empirical mode decomposition techniques for classification and extracting block of backbone components using deep CNN approach. Context-aware attention classifies the main features of pneumonia cases which helps to detect COVID-19.…”
Section: Literature Studymentioning
confidence: 99%
“…Specifically, Varzaneh et al . [ 8 ] evaluated various of the classical ML algorithms in terms of their ability to predict patients’ need for intubation due to an adverse progression of COVID-19. In a similar manner, several models have been proposed to predict mortality risk: Caillon et al .…”
Section: Introductionmentioning
confidence: 99%